Study on the phase composition and structure of hardened cement paste during heat treatment. (6th December 2021) - Ji, Xiaomin; Ji, Daopeng; Yang, Zhouxiang; Wang, Guoling; Huang, Xiaofei; Ma, Suhua; Li, Weifeng
Highlights: The C-S-H in the HCP is dehydrated at about 600–800 °C to form active C2 S. α'-C2 S and β-C2 S has higher hydration activity than C2 S formed at high temperatures. Dehydration phase rehydration can stimulate coal gangue pozzolanic activity. Composite reclaimed cementitious material has excellent mechanical properties. Abstract: To utilize the fine powder produced in the process of preparing recycled concrete or recycled aggregate, the phase composition and structure of hardened cement paste during calcination at low temperature are investigated in this paper. Results show that as the temperature increases, both ettringite and AFm decompose to form C12 A7, CaSO4 and CaCO3 . Hydrated calcium silicate is dehydrated to form highly active α'-C2 S at 600 °C. α'-C2 S has higher hydration activity than C2 S formed at high temperatures. When the temperature continues to increase to 800 °C, α'-C2 S begins to transform into β-C2 S. The dehydration phase at 700–800 °C has the best activity. At the same time, cement paste will inevitably produce more CaO during the heat treatment process. and the Ca(OH)2 generated when it meets with water can be used to stimulate the pozzolanic activity of the calcined coal gangue. To prepare recycled cementitious materials with high strength and excellent performance.